Pirmoji Lietuvos archeologinė ekspedicija Afganistane - Luchtanas, Aleksiejus; Butrimaitė, Ramunė (Lietuvos istorijos studijos, 2008)
Afghanistan is most considerable for its historical, political, and geographical situation, however this region of Central Asia is least explored. The country falls into the sphere of East Iran and Indo valley cultures influence. Afghanistan carries its rich history, which reflects in most monuments of culture. The earliest records of Afghanistan's cultural heritage are the accounts of travelers, first Chinese, then Muslim, and finally European. Interest in Afghanistan's cultural heritage grew in the 20th century with the archaeological expeditions provided by Italian, Indian, German, Japanese, Russian, French, and American scientists. The end of the 20th century was marked by the regression of activities in the cultural sphere. Only after 2001 did the works of heritage reestablishment begin. The priority of the Afghanistan government and UNESCO is the search, documentation, and registering of cultural heritage sites.With the creation of the International Security Assistance Force (ISAF) in Afghanistan and the establishment of the provincial reconstruction team in Ghor province, conducted by Lithuania, civilian projects related to culture, education, and health services are being carried on. In 2007, the Center of Archaeological Projects "Antiqua" started an archaeological heritage mission related to the search, survey, and registration of archaeological remains in the province of Ghor. The search for new archaeological sites, according to the maps, was carried out within a 30-40 km radius around Chaghcharan (the center of the province). During the expedition, 14 new cultural valuables and their complexes, situated on the banks of the Hari Rud river, were found. According to the fragments of pottery discovered at the sites, the cultural valuables are dated back to the 4th millennium BC to the XIX/XX centuries AD. These are complexes of ancient settlements, usually called tapa (Purnbakar, Ahangaran, Sheke, Puzei-Leče), dated 4th millennium BC-XX AD, fortified towns (Farizkuh, Qala Mana), dated XI-XIII AD, castles and defensive towers (Qala Akbar Bek Zahak, Qala Malek Antar, Qala Kassi, Qala Kuhna, Shinia, Badgha), dated VI-XIX AD, and historic industrial objects such as brickfields, mills, caravanserais, and bridges.Many of the surveyed cultural valuables are not only undescribed and unregistered, but are also under the destruction of illegal excavations, natural forces, and farming. Most Afghan people still live and use some cultural monuments, applying long-lasting, changeless farming systems.